Barriers and recommendations for harm reduction services among people living with HIV in Manitoba, Canada: a qualitative study - Villacis-Alvarez, Enrique; Maier, Katharina; Haworth-Brockman, Margaret; Pashe, Heather; Baliddawa, Joel; Daniels, Nikki; Murdock, Rebecca; Russell, Robert; Dan, Clara; Woodhouse, Freda; Cusson, Susie; Schenkels, Marj; et al. (Frontiers in Public Health, 2025)
IntroductionIn 2022, the province of Manitoba, Canada, recorded its highest increases in substance-related deaths and new HIV diagnoses. The COVID-19 pandemic exacerbated access barriers to harm reduction services across the country. Given the intertwined relationship between HIV and injection substance use, we sought to better understand People Living with HIV’s (PLHIV) access barriers to harm reduction services, and recommendations for improved care.MethodsThis qualitative study was co-designed by and co-executed with people with lived experiences in HIV and substance use. The data collection process encompassed a semi-structured in-depth qualitative interview with PLHIV followed by three quantitative questionnaires and was conducted between October 2022 and May 2023 in HIV clinics. Descriptive statistics were performed to illustrate substance use practices, and we employed reflexive thematic analysis to generate themes and explain shared patterns of meaning across participants in relation to our research question.ResultsWe developed two themes to explain the qualitative data: (1) knowledge about and availability of harm reduction services, and (2) safer substance use and supervised consumption sites. In the first theme, participants described being aware of the different harm reduction services in their community, but recounted several access barriers limiting service uptake, including restrictive service times and limited mobile services. These limitations increased participants’ likelihood of sharing injecting equipment, and produced stress and anxiety about lacking access to safe supplies. In the second theme, participants discussed what they consider “safe” spaces for using substances, highlighting the importance of autonomy and privacy where they can use without fear of stigma and interference. Thus, to make substance use safer in Manitoba, participants advocated for the implementation of supervised consumption sites to ensure the availability of non-judgmental spaces where they can find and use safe injecting supplies, trained staff, and connections to health and social supports.DiscussionPLHIV who use substances face many hurdles when seeking harm reduction and health services. It is essential to implement new strategies centred on the lives of PLHIV who use substances to address the unprecedented rates of HIV diagnoses, health-related harms, and substance-related deaths.